Imaging, modeling and assimilation in seismology - Li, Yong-Gang (De Gruyter, 2012)
This work presents current approaches in geophysical research of earthquakes. A global authorship from top institutions presents case studies to model, measure, andmonitor earthquakes. Among others afull-3D waveform tomography method is introduced, as well as propagator methods for modeling and imaging. In particular the earthquake prediction method makes this book a must-read for researchers in the field.